2022
DOI: 10.3389/fendo.2022.860634
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Serum Palmitic Acid and Thyroid Function

Abstract: AimEmerging evidence indicates that palmitic acid (PA) can regulate the progression and development of many diseases. However, the studies examining the association between PA and thyroid function remain sparse. We aimed to investigate the association between serum PA (sPA) and thyroid function in the US population.MethodsIn this retrospective study, a cross-sectional analysis was performed using the data pooled from the database of the National Health and Nutrition Examination Survey (NHANES) from 2011 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In a cross-sectional study, Zhou et al [20] examined the relationship between serum palmitic acid and thyroid function in the United States population using the database of the National Health and Nutrition Examination Survey from 2011 to 2012. They identified a significant negative association between serum palmitic acid and free T4 [20]. In our study, methimazole-naïve patients had an elevated serum level of palmitic acid Copyright © 2022 Korean Endocrine Society and this was decreased after methimazole treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional study, Zhou et al [20] examined the relationship between serum palmitic acid and thyroid function in the United States population using the database of the National Health and Nutrition Examination Survey from 2011 to 2012. They identified a significant negative association between serum palmitic acid and free T4 [20]. In our study, methimazole-naïve patients had an elevated serum level of palmitic acid Copyright © 2022 Korean Endocrine Society and this was decreased after methimazole treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with an inverse relationship between thyroid activity and the percentage levels of palmitic acid in FFAs. In a cross-sectional study, Zhou et al [ 20 ] examined the relationship between serum palmitic acid and thyroid function in the United States population using the database of the National Health and Nutrition Examination Survey from 2011 to 2012. They identified a significant negative association between serum palmitic acid and free T4 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…4-HBA in serum samples could be derived from the catechin metabolism of green tea, which is involved in ubiquinone biosynthesis in humans and could inhibit oxidative stress, thus protecting neuronal cells in neurodegeneration [41]. PA is a major fatty acid existing in human blood and retina and interferes with multiple normal biological functions, including protein palmitoylation and PEA biosynthesis [42,43], which, in turn, influence the oligodendrocyte differentiation and are involved in age-related neurodegenerative disorders [44]. Our results of lower serum PA and faecal PEA levels in the nAMD group highly indicated that diet-nutrition-adjustment treatment could improve the neuroprotective metabolites in nAMD patients and provide remission of the AMD disease process.…”
Section: Discussionmentioning
confidence: 99%
“…There are three main iodothyronine deiodinases in the body: iodothyronine deiodinase 1 (DIO1) and iodothyronine deiodinase 2 (DIO2) 5′-deiodinases catalyzes the activation reaction from T4 to T3, iodothyronine deiodinase 3 (DIO3) 5-deiodinase catalyzes the activation reaction from T4 inactivation response to reverse T3 (10). FT3/FT4 reaction 5'-deiodinase activity can be used to evaluate peripheral thyroid sensitivity (2,(11)(12)(13)(14). The FT3/FT4 ratio seems to be a precise and reasonable indicator of thyroid hormone metabolic change that is associated with the prognosis of specific diseases, including coronary heart disease (CHD), myocardial infarction (MI), and dilated cardiomyopathy (DCM) (15-18).…”
Section: Introductionmentioning
confidence: 99%